Varieties of capitalism, varieties of approaches - Coates, David (Palgrave Macmillan, 2005)
Written by major participants in the key debates in comparative political economy, 12 essays explore underlying theoretical issues involved in the analysis of advanced capitalism. In particular, they reflect upon the debates triggered by Hall and Soskice's Varieties of Capitalism and those responding to Bob Brenner's article "The Economics of Global Turbulence." The papers were originally presented at a 2002 conference held at Wake Forest U. in North Carolina.